CALCIUM SOURCES AND CONCENTRATIONS AFFECTING TOMATO FRUIT QUALITY STORED IN DIFFERENT STORAGE CONDITIONS - B. Haleema; A. Rab (Journal of Animal and Plant Sciences, 2018)
Experiment was conducted in Biochemistry Laboratory of Agriculture Research Institute Tarnab (ARI), Peshawar during the year 2014 in a completely randomized design with three replications. The treatments comprised of Ca sources (calcium chloride, calcium gluconate, calcium lactate and calcium sulphate), with different Ca concentrations ( 0, 0.25, 0.5 and 0.75%) in two storage conditions; 32±2°C and 10± 2°C. The results revealed higher incidence of soft rot and black rot when fruits were stored at ambient temperature. Cell wall ion leakage, cell membrane ion leakage and incidence of green mold were higher with low temperature storage. Likewise, higher Ca content was recorded with calcium chloride. However, cell wall ion leakage and cell membrane ion leakage were lower in calcium chloride. The Ca content of tomato fruit was higher with 0.75% Ca concentration. The cell wall ion leakage and cell membrane ion leakage were recorded least at 0.75% concentration of calcium. The least and same incidence of black rot and were recorded at 0.5 and 0.75% Ca concentration respectively while the incidence of soft rot and green mold was found to be at minimum in 0.75% Ca concentration. respiration rate and ethylene production, delay ripening,
Keywords: Black rot; calcium sources; calcium concentrations; ion leakage; storage temperature; soft rot; green mold.